Developing methylotrophic microbial platforms for a methanol-based bioindustry - Singh, Hawaibam Birla; Kang, Min-Kyoung; Kwon, Moonhyuk; Kim, Seon-Won (Frontiers in Bioengineering and Biotechnology, 2022)
Methanol, a relatively cheap and renewable single-carbon feedstock, has gained considerable attention as a substrate for the bio-production of commodity chemicals. Conventionally produced from syngas, along with emerging possibilities of generation from methane and CO2, this C1 substrate can serve as a pool for sequestering greenhouse gases while supporting a sustainable bio-economy. Methylotrophic organisms, with the inherent ability to use methanol as the sole carbon and energy source, are competent candidates as platform organisms. Accordingly, methanol bioconversion pathways have been an attractive target for biotechnological and bioengineering interventions in developing microbial cell factories. This review summarizes the recent advances in methanol-based production of various bulk and value-added chemicals exploiting the native and synthetic methylotrophic organisms. Finally, the current challenges and prospects of streamlining these methylotrophic platforms are discussed.